Chancer. Series 1 [videorecording (DVD)] - Grint, Alan; Moody, Laurence; Owen, Clive; Phillips, Leslie, 1924-; Vaughan, Peter, 1923-2016; Harker, Susannah; Shepherd, Simon (Distributed by Acorn Media, 2007)
Stephen Crane is a con artist, swindler, and purported savior of a struggling sports car company. Sacked from an investment bank after one dodgy deal too many, Stephen lands a job at Douglas Motors, a business distinguished by old-fashioned craftsmanship and plagued by decades of familial mismanagement. There he finds himself playing surrogate son to the family patriarch, confidant to the adulterous son-in-law, and lover to the beautiful but willful daughter. All the while, he fends off forays from his erstwhile boss, a deliciously evil banker bent on recovering a bunch of swindled money. But, can Stephen keep his double-dealing past at bay?